Classic Performing Arts Supply Chain Modeling in Covid 19 Protocol to Support D.I Yogyakarta Cultural Tourism Using Soft System Methodology - Indrayana, Masrul (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The performing arts are a unique and complex industry. To enjoy performing arts products, a customer must come to the rooms where the performance takes place. Performance products can be categorized as service products that do not have a physical form. Every performing arts performance always involves many works of art with a high level of coordination. The flow of materials and information (supply chain) moves very quickly within the limitations of space and time. Because the success of performing arts is influenced by many factors and actors, a performing arts manager must be able to manage the performing arts supply chain well.The Corona Virus Disease 19 (Covid-19) pandemic which has hit almost all corners of the world has formed new patterns of human behavior in working and interacting. Likewise, organizing and enjoying performing arts will look different compared to before the Covid-19 outbreak. The implementation of health protocols is needed to minimize the spread of the virus which has infected more than 13.2 billion people throughout the world.The performing arts supply chain policy model in the Covid-19 protocol to support cultural tourism in D.I Yogyakarta can be implemented by following the Joint Decree Guidelines of the Minister of Education and the Minister of Tourism and Economy dated 02 July 2020. Each actor must pay attention to the technical guidelines for preventing and controlling corona virus disease 2019. Each actor guarantees the hygiene of their respective performing arts equipment. Each actor maintains the form and duration of physical contact and pays attention to health protocols in activities throughout the performing arts supply chain. The performing arts model during the pandemic is realized in regulations that are in accordance with the technical guidelines for preventing and controlling the 2019 corona virus disease.